The effect of Nordmøre grid length and angle on codend entry of bycatch fish species and shrimp catches - Larsen, Roger B.; Sistiaga, Manu Berrondo; Herrmann, Bent; Brinkhof, Jesse; Tatone, Ivan; Santos, Juan (Canadian Journal of Fisheries and Aquatic Sciences, 2018)
Accepted manuscript version. Published version available at https://doi.org/10.1139/cjfas-2018-0069 . The Nordmøre grid is regarded as an efficient bycatch reducing device and is used in various shrimp trawl fisheries globally. However, in some shrimp fisheries bycatch remains a problem that seriously impacts commercial trawl activities. This study tested and compared the performance of two versions of the Nordmøre grid in the Northeast Arctic Deepwater Shrimp (Pandalus borealis) fishery; a standard version with an operating angle of ca. 45° and a longer version of the grid (40% longer) with an operating angle of ca. 30°. The grid passage probability for the bycatch of juvenile Cod, Haddock, American Plaice and Redfish increased significantly for certain size ranges of fish when using the longer grid. The longer grid also resulted in a significant increase in grid passage probability for large shrimp. Previous studies have reported that a reduced operating angle can lead to a lower grid passage probability for bycatch fish species and shrimp, however the results of the current study demonstrate that a longer Nordmøre grid more than compensates for the reduced operational angle.